2016
DOI: 10.1016/j.jsxm.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Testosterone Solution 2% on Ejaculatory Dysfunction in Hypogonadal Men

Abstract: Introduction Hypogonadism is defined as decreased testosterone levels in men. Hypogonadism can be accompanied by erectile, orgasmic, and ejaculatory dysfunction. Aims To evaluate whether treatment with testosterone solution 2% (testosterone) could improve ejaculatory function in a cohort of hypogonadal men. Methods Sexually active, hypogonadal men at least 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…Both experimental and clinical studies have documented that T is profoundly involved in the regulation of the male ejaculatory reflex [50]. In line with our finding, a recent, large, placebo-controlled trial performed on more than 700 patients documented that a 2% transdermal T solution was able to improve orgasmic and ejaculatory function, although the associated bother did not improve [51].…”
Section: Discussionsupporting
confidence: 90%
“…Both experimental and clinical studies have documented that T is profoundly involved in the regulation of the male ejaculatory reflex [50]. In line with our finding, a recent, large, placebo-controlled trial performed on more than 700 patients documented that a 2% transdermal T solution was able to improve orgasmic and ejaculatory function, although the associated bother did not improve [51].…”
Section: Discussionsupporting
confidence: 90%
“…However, as for MSHQ total score, a minimum clinically meaningful change in ejaculation domain scores is yet to be determined. Previous studies have shown sensitivity of the total MSHQ scores to both diagnostic status and treatment conditions . The post hoc correlation analyses between sexual activity/desire and ejaculation, erection, and satisfaction domains were all in the expected direction, and in line with previously described correlations between sexual desire, erectile dysfunction, and sexual satisfaction …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the absolute changes from baseline and the differences at 12 months between placebo and the DUT‐TAM FDC therapy group, for the erection and overall satisfaction domains, were numerically very small and unlikely to be clinically relevant. Previous studies have shown the sensitivity of total MSHQ scale scores to both diagnostic status and treatment conditions . The ejaculation domain subscale of the MSHQ has shown treatment sensitivity to pharmacological and other treatments of BPH , although a minimum clinically meaningful change in ejaculation has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%